ATIVIDADE GRUPAL COMO INSTRUMENTO DE INSERÇÃO SOCIAL: VIVÊNCIAS COM GRUPOS DA TERCEIRA IDADE - Sassi, Marcelo M.; Dalmolin, Indiara S.; Perdonssini, Leila B.; Leite, Marinês T.; Nardino, Janaine; Hildebrandt, Leila M. (Salão do Conhecimento, 2013)
Resumo